2011
DOI: 10.1126/scitranslmed.3001756
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Testing for Severe Childhood Recessive Diseases by Next-Generation Sequencing

Abstract: Of 7028 disorders with suspected Mendelian inheritance, 1139 are recessive and have an established molecular basis. Although individually uncommon, Mendelian diseases collectively account for ~20% of infant mortality and ~10% of pediatric hospitalizations. Preconception screening, together with genetic counseling of carriers, has resulted in remarkable declines in the incidence of several severe recessive diseases including Tay-Sachs disease and cystic fibrosis. However, extension of preconception screening to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
509
5
15

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 622 publications
(538 citation statements)
references
References 48 publications
9
509
5
15
Order By: Relevance
“…Carrier screening may reduce the incidence of DMD and ameliorate the suffering associated with DMD. 22 DMD female carriers are prone to developing cardiomyopathy, which can be effectively prevented and treated if the carriers are diagnosed early and followed-up routinely. 23 Indeed, many experts advocate DMD screening in all newborns for diagnosis as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Carrier screening may reduce the incidence of DMD and ameliorate the suffering associated with DMD. 22 DMD female carriers are prone to developing cardiomyopathy, which can be effectively prevented and treated if the carriers are diagnosed early and followed-up routinely. 23 Indeed, many experts advocate DMD screening in all newborns for diagnosis as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…42,[49][50][51][52][53][54][55] Many variants that have previously been reported as pathogenic in the medical literature (and thus are represented in databases used for molecular DNA analysis) are now known to have allele frequencies that make them very common occurrences in the general population, or they have been seen in the homozygous state in healthy controls. [56][57][58] Large polymorphic genes, such as the ABCA4 gene associated with Stargardt disease, arRP, autosomal-recessive CRD, and cone dystrophy, are likely to contain more variants that require scrutiny because some variants may have been previously erroneously asserted as being pathogenic. 59 When the appropriate level of evidence is not present to classify a variant as known/likely benign or deleterious, the laboratory must classify the variant as a "variant of unknown significance. "…”
Section: Variant Interpretationmentioning
confidence: 99%
“…In 2011, an NGS study demonstrated the clinical and analytic validity of exome sequencing targeting a preselected region known to be associated with severe childhood autosomal recessive diseases, like Tay-Sachs disease and cystic fibrosis (Bell et al, 2011). Yin et al (2013) introduced a method of massively parallel sequencing for aneuploidy of blastocysts, reporting a 68.4% euploidy rate.…”
Section: Routine Preimplantation Genetic Screening (Pgs) In Gestationmentioning
confidence: 99%